Cellular, transcriptomic and methylome effects of individual and combined exposure to BPA, BPF, BPS on mouse spermatocyte GC-2 cell line - Sidorkiewicz, Iwona; Czerniecki, Jan; Jarząbek, Katarzyna; Zbucka-Krętowska, Monika; Wołczyński, Sławomir (Toxicology and applied pharmacology, 2018)
Environmental factors, particularly xenoestrogens adversely affect reproductive health and their main mechanism is based on steroid-signaling pathway alterations. The presence of bisphenol A (BPA) in the environment has been confirmed and it is about to be replaced by analogues such as bisphenol F (BPF) and bisphenol S (BPS). Whether the BPF and BPS exert similar adverse effects to BPA has become the subject of intense scientific scrutiny. The aim of the present study was to evaluate and compare the cellular, transcriptomic and methylome effects of exposure to BPA, BPF, BPS individually and in combination on GC-2 spermatocyte cell line. The results show that all studied compounds affect cell viability, induce apoptosis and cause cellular damage. BPA, BPF and BPS also influence GC-2 cell steroid receptor and steroidogenesis related genes expressions. In addition to specific molecular mechanisms, all studied compounds also increase global DNA methylation. Exposure to a combination of all the studied compounds caused comparable effects on cell culture to each of them examined separately. These data suggest that exposure to BPA and its main substitutes- BPF and BPS induced multitude of effects and hence, BPF and BPS are not safe alternative to BPA in terms of male reproductive health. •BPA, BPF and BPS affect GC-2 cell viability•ERs and GPR30 cooperate in mediating the effects of BPF and BPS•Mixture of bisphenols causes comparable effects as single compound.•BPA, BPF and BPS affect global DNA methylation.•BPF and BPS are not safe substitutes to BPA.